School absenteeism, work and health among Brazilian children: Full information versus limited information model - Danielle Carusi Machado; Carine Milcent; Jacques Huguenin (EconomiA, 2013)
We estimate a system of three behavioral equations for Brazilian children and teenagers (school absenteeism, health status and child labor). We relieved the assumption of independence of the disturbance terms of each equation. Moreover, if causality mechanisms between these three components (school absenteeism, health status and child labor) can occur either way, it can also be the result of a simultaneous decision-making process. Thus, to take into account both endogenous causality aspects and simultaneity, we estimate using the FIML method, which provides some improvement to the quality of the estimation, allowing us to simultaneously estimate all relevant parameters, including covariance parameters, and also to the subsequent interpretation of the results. – – Estimamos um sistema com três equaç\~oes comportamentais para crianças e adolescentes do Brasil (absenteísmo escolar, status da saúde e trabalho infantil). Relaxamos a hipótese de independência dos termos de erro de cada equaç\~ao. Se os mecanismos de causalidade entre estes três componentes (absenteísmo escolar, status da saúde e trabalho infantil) podem ocorrer em qualquer direç\~ao, também podem ser resultantes do processo de escolha simultânea. Desta forma, para considerar tanto os aspectos relacionados à causalidade endógena quanto os de simultaneidade, estimamos usando o método FIML, que melhora a qualidade da estimaç\~ao, permitindo a estimaç\~ao simultânea de vários parâmetros relevantes, incluindo os parâmetros da matriz de variância-covariância, e também a interpretaç\~ao dos resultados.
Keywords: I12; J13; J18; J24; 330; Children; Education; Health; Work; Limited information model; Full information model